Increasing the Efficiency of Pedagogical Activity: Structural and Functional Approach - Kuddusovna, Rakhmonova Sharofat (International Journal of Psychosocial Rehabilitation, 2020)
The article analyzes the structural and functional approaches to the ongoing reforms in the higher education system of Uzbekistan, including the “Concept of Higher Education Development” and the gradual implementation of its priorities, educational programs and distance learning were analyzed. Moreover, the essence of modern higher education and the tasks set for it, to ensure the quality of education for the education of human- professional personality, to strengthen the stratified approach to ensure continuity of education in educational institutions, individual approach to education and the formation of pedagogical and pedagogical qualities, the factors of increasing team responsibility, a scientific approach to the student’s personality, and personality development are highlighted.